Mexican-Origin Parents’ Work Conditions and Adolescents’ Adjustment - Wheeler, Lorey A. (J Fam Psychol, 2015)
Mexican-origin parents’ work experiences are a distal extra-familial context for adolescents’ adjustment. This two-wave multi-informant study examined the prospective mechanisms linking parents’ work conditions (i.e., self-direction, work pressure, workplace discrimination) to adolescents’ adjustment (i.e., educational expectations, depressive symptoms, risky behavior) across the transition to high school drawing on work socialization and spillover models. We examined the indirect effects of parental work conditions on adolescent adjustment through parents’ psychological functioning (i.e., depressive symptoms, role overload) and aspects of the parent-adolescent relationship (i.e., parental solicitation, parent-adolescent conflict), as well as moderation by adolescent gender. Participants were 246 predominantly immigrant, Mexican-origin, two-parent families who participated in home interviews when adolescents were approximately 13 and 15 years of age. Results supported the positive impact of fathers’ occupational self-direction on all three aspects of adolescents’ adjustment through decreased father-adolescent conflict, after controlling for family socioeconomic status and earner status, and underemployment. Parental work pressure and discrimination were indirectly linked to adolescents’ adjustment, with different mechanisms emerging for mothers and fathers. Adolescents’ gender moderated the associations between fathers’ self-direction and girls’ depressive symptoms, and fathers’ experiences of discrimination and boys’ risk behavior. Results suggest that Mexican-origin mothers’ and fathers’ perceptions of work conditions have important implications for multiple domains of adolescents’ adjustment across the transition to high school.